2014
DOI: 10.14504/ajr.1.6.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Washfastness and Crockfastness Values: Pigment Printed Fabrics

Abstract: Washfastness and crockfastness values were evaluated to study the effects of binder and process parameters on pigment printing. Acrylate-and butadiene-based binders, and three different colorants, were used for pigment printing on 100% cotton fabrics. Sixty-six pigment printed fabrics were evaluated for washfastness and crockfastness by standard test methods. Fastness values were evaluated based on binder, softener, fixator, process, fastness developer, pH, and curing temperature/ time. Results indicated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…However, excessive film thickness would have serious effects on the structure and porosity of the original fabric, leading to stiffening, poor air permeability, and low dry and wet crocking colour fastness. 16,17…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, excessive film thickness would have serious effects on the structure and porosity of the original fabric, leading to stiffening, poor air permeability, and low dry and wet crocking colour fastness. 16,17…”
mentioning
confidence: 99%
“…However, excessive film thickness would have serious effects on the structure and porosity of the original fabric, leading to stiffening, poor air permeability, and low dry and wet crocking colour fastness. 16,17 In recent years, it has been discovered that organic material hybrid pigments can greatly improve the performance instability of pigments, such as their dispersibility, light resistance, and thermal stability properties. [18][19][20][21][22][23][24][25][26][27] For example, Fu et al [23][24][25] reported that the adhesion fastness of pigment particles with the fabric can be significantly improved after coating with polyacrylate (PAcr).…”
mentioning
confidence: 99%
“…As shown in Figure a, migration and aggregation of pigment particles generally occur during film formation. Uneven distribution affects the binding ability between the pigment and fiber, and pigment aggregation at the micron scale decreases color depth, color fastness, and color uniformity …”
Section: Introductionmentioning
confidence: 99%
“…Uneven distribution affects the binding ability between the pigment and fiber, and pigment aggregation at the micron scale decreases color depth, color fastness, and color uniformity. 12 One strategy for improving the performance of pigment dyed/printed fabrics is binder-free pigment dyeing/printing of textiles using polymer/pigment hybrid latex. 13,14 Several studies have explored the use of emulsion polymerized copolymerencapsulated pigment hybrid latex particles instead of blended pigment and adhesive latex.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A binder is necessarily employed to fix the pigment onto the textiles properly 32,33 . Sometimes a high dosage of binders is required to ensure the qualified fastness of the printed fabrics with deep colors, while it inevitably leads to stiff hand and limits its wide application in printing 34‐37 . To address this issue, a novel sustainable printing approach, namely washing‐free disperse dye printing (WFP), has been developed through using disperse dyes instead of pigments 38,39 .…”
Section: Introductionmentioning
confidence: 99%